The Effect of Profitability and Company Size on Audit Delay During The Pandemic in Consumer Goods Company - Siti Nuridah; Nirwan Nirwan; Siti Ayu Rosida; Pradnya Sari Harsanti; Wulandari Wulandari (ProBisnis : Jurnal Manajemen, 2023)
The main purpose of this study is to know the influence of profitability and companies’ size on audit delay during the pandemic in consumer goods companies. The profitability within this study is proxied by the return on assets while the measurement company is proxied by the logarithm of natural assets. This study was conducted during the pandemic, from 2020 to 2021. The research used a method of panel data regression analysis. The sample was taken based on the purposive sampling method with 39 companies. The analysis tool used eviews version 10. Finally, the results of this study show that 1) Profitability negatively effect on audit delay: the higher of the profitability value, the lower of the audit delay, 2) Company size positively effect on audit delay: the higher of total assets of the company, the higher of the audit delay, 3) Profitability and firm size affected on the audit delay.